2021
DOI: 10.1108/ijph-04-2020-0020
|View full text |Cite
|
Sign up to set email alerts
|

A social ecological model (SEM) to exploring barriers of and facilitators to the implementation of opioid agonist treatment (OAT) programmes in prisons

Abstract: Purpose Opioid agonist treatment (OAT) programmes in prisons play a significant role in preventing the human immunodeficiency virus (HIV). Despite its proven effectiveness, both the availability and coverage of prison OAT programmes remain low. This Indonesian study explores facilitators of, and barriers to, the delivery of methadone programmes in prisons using the social ecological model (SEM). Design/methodology/approach The study used a qualitative case study approach comprising two prisons with, and one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…This finding supports the argument of who advocates the importance of judges making decisions that reflect the condition of women who are already experiencing socioeconomic problems. This involves displaying a sensitivity that involves exercising discretion and encouraging participants to redefine sentencing options outside prison (Komalasari et al, 2021a). These participants sought to reduce sentences with the aim of releasing women drug users from prison earlier than required by law and allowing them to receive treatment outside prison.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding supports the argument of who advocates the importance of judges making decisions that reflect the condition of women who are already experiencing socioeconomic problems. This involves displaying a sensitivity that involves exercising discretion and encouraging participants to redefine sentencing options outside prison (Komalasari et al, 2021a). These participants sought to reduce sentences with the aim of releasing women drug users from prison earlier than required by law and allowing them to receive treatment outside prison.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that DTTO II is overused with women even though there are fewer women in the Criminal Justice System. (49% of women received DTTO II) compared to men (51%) (Komalasari et al, 2021a). This is partly a reflection of DTTO II targeting low-rate violators (Malloch 2011).…”
Section: Drug Treatment and Testing Orders (Dtto Ii)mentioning
confidence: 99%
See 1 more Smart Citation
“…Linkage to care in the community poses another significant challenge to PrEP care among criminal justice–involved individuals. Currently, providing continuity of care for both pretrial individuals as well as those sentenced to a period of confinement poses a challenge, particularly for those who are HIV-positive, are impacted by substance use disorder, or have general medical needs [ 49 , 50 ]. The availability and accessibility of PrEP care providers is likely to vary significantly based on geographic region, an individual’s insurance status, and the existence of other health linkage programs unrelated to PrEP care [ 51 , 52 ].…”
Section: Methodsmentioning
confidence: 99%
“…Socioecological approaches allow for the exploration of issues across five levels: individual, intrapersonal, organisational, community and policy [ 38 ]. Such models are increasingly used to study public health issues, including opioid use and dependency (e.g., [ 39 , 40 , 41 , 42 , 43 , 44 ]). However, only a small number of studies have adopted this approach to specifically explore experiences of OAT [ 39 , 45 , 46 ], and, to our knowledge, no studies have been conducted in a UK treatment context.…”
Section: Introductionmentioning
confidence: 99%